The definitive characteristics of throttle accelerators and their differences for other philanthropic organizations (Revista Brasileira de Contabilidade e Gestão, 2017)
The first accelerators appeared in the last decade. Since they’re a relatively recent phenomenon, the research on them is also quite new. However, there are some researchers, notably Susan Cohen and Yael V. Hochberg, that have been able to establish a good framework when it comes to the definition and nuances of accelerators. This article proposes to exhibit the main themes these authors discuss, showing the different types and characteristics of accelerators, as well as their differences to other philanthropic organizations (incubators and angel investors).
Keywords: startup; accelerator; startup accelerator